2007
DOI: 10.1196/annals.1409.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Genetic Manipulation in Francisella Tularensis

Abstract: Francisella tularensis is a gram-negative coccobacillus and the etiological agent of tularemia. The limited knowledge regarding the interaction of F. tularensis with its host is due in part to the previous lack of tools for genetically manipulating the organism. During the past 10 years, the field of F. tularensis genetics has seen a rapid expansion. Plasmids capable of stable or conditional replication in Francisella have been constructed. Methods for the efficient introduction of DNA into Francisella have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…Plasmid DNA was purified from E. coli using the QIAprep Spin Miniprep Kit (QIAGEN, Valencia, CA). The chemical transformation protocol used to introduce pSC-1423/1422K into F. novicida was based on a combination of previously described methods (Frank and Zahrt, 2007; Gallagher et al, 2008). An overnight culture of F. novicida grown on CDMA was suspended in 1 ml of phosphate buffered saline (PBS), pH 7.6.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid DNA was purified from E. coli using the QIAprep Spin Miniprep Kit (QIAGEN, Valencia, CA). The chemical transformation protocol used to introduce pSC-1423/1422K into F. novicida was based on a combination of previously described methods (Frank and Zahrt, 2007; Gallagher et al, 2008). An overnight culture of F. novicida grown on CDMA was suspended in 1 ml of phosphate buffered saline (PBS), pH 7.6.…”
Section: Methodsmentioning
confidence: 99%
“…This has led to a surge of studies of this human pathogen in an attempt to better understand the pathogenesis of the bacteria and to design novel approaches for diagnostics, prophylaxis, and treatment strategies. Such studies strongly depend on the availability of genetic tools that enable the examination of individual bacterial proteins in a variety of experimental approaches (e.g., directed disruption of genes and/or controlled expression of heterologous proteins), and the paucity of these tools severely limited F. tularensis research for many years (10). We therefore decided to search for, isolate, and characterize different F. tularensis promoters to increase the number of genetic tools that will allow the modulation of gene expression in the background of F. tularensis.…”
mentioning
confidence: 99%
“…The unique presence of this barrier in F. novicida suggests that restriction may have been lost in the evolution of the more virulent lineages. The barrier is also of practical importance, for it has made genetic manipulations such as plasmid transformation and gene targeting in F. novicida challenging (7). In this study we have identified the principle determinants of restriction in F. novicida and have constructed a multiple mutant in which the restriction barrier is fully eliminated.…”
mentioning
confidence: 99%